Capping with activated carbon reduces nutrient fluxes, denitrification and meiofauna in contaminated sediments. (1st January 2019) - Bonaglia, Stefano; Rämö, Robert; Marzocchi, Ugo; Le Bouille, Léonie; Leermakers, Martine; Nascimento, Francisco J.A.; Gunnarsson, Jonas S.
Abstract: Sediment capping with activated carbon (AC) is an effective technique used in remediation of contaminated sediments, but the ecological effects on benthic microbial activity and meiofauna communities have been largely neglected. This study presents results from a 4-week experiment investigating the influence of two powdered AC materials (bituminous coal-based and coconut shell-derived) and one control material (clay) on biogeochemical processes and meiofauna in contaminated sediments. Capping with AC induced a 62–63% decrease in denitrification and a 66–87% decrease in dissimilatory nitrate reduction to ammonium (DNRA). Sediment porewater pH increased from 7.1 to 9.0 and 9.7 after addition of bituminous AC and biomass-derived AC, respectively. High pH (>8) persisted for at least two weeks in the bituminous AC and for at least 24 days in the coconut based AC, while capping with clay had no effect on pH. We observed a strong impact (nitrate fluxes being halved in presence of AC) on nitrification activity as nitrifiers are sensitive to high pH. This partly explains the significant decrease in nitrate reduction rates since denitrification was almost entirely coupled to nitrification. Total benthic metabolism estimated by sediment oxygen uptake was reduced by 30 and 43% in presence of bituminous coal-based AC and coconut shell-derived AC, respectively. Meiofauna abundances decreased by 60–62% in the AC treatments. Taken together, these observations suggest that AC amendments deplete natural organic carbon, intended as food, to heterotrophic benthic communities. Phosphate efflux was 91% lower in presence of bituminous AC compared to untreated sediment probably due to its content of aluminum (Al) oxides, which have high affinity for phosphate. This study demonstrates that capping with powdered AC produces significant effects on benthic biogeochemical fluxes, microbial processes and meiofauna abundances, which are likely due to an increase in porewater pH and to the sequestration of natural, sedimentary organic matter by AC particles. Graphical abstract: Highlights: Capping with activated carbon (AC) has pronounced effects on sediment geochemistry. AC significantly increases porewater pH, an effect that lasts for several weeks. Total benthic metabolism and microbial denitrification are drastically reduced. AC increases mortality of meiofauna and alters community composition. The main causes may be pH increase and sequestration of natural organic matter.